The effect of Prewetting on the Pressure Drop, Liquid Holdup and Gas-Liquid Mass Transfer in Trickle-Bed Reactors - Nicol, Willie (University of Pretoria, 2013)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2007.